A Mass Spectrometric Approach to the Proteomic Profiling of the Canis lupus familiaris Acquired Enamel Pellicle on Hydroxyapatite Discs. (September 2022) - M. Grant, Melissa; Pasha, Sabah; Inui, Taichi; Chapple, Iain; Harris, Steve; Holcombe, Lucy
The acquired enamel pellicle (AEP) is a multi-protein film attached to the surface of teeth, which functions to lubricate the dental surface, form an anti-erosive barrier and exhibits antimicrobial properties. The initiation of AEP formation occurs within seconds of exposure to saliva, a biofluid rich in protein species. While there have been many publications on the formation of human AEP there is little research on the composition of canine AEP during its acquisition. The aim of these studies was to explore the composition of canine AEP formation, utilising hydroxyapatite (HA) discs as a tooth substitute matrix, over time. Qualitative and quantitative proteomics techniques using tandem mass tag labelled peptides and LC-MS/MS were used to follow the formation of canine AEP on hydroxyapatite discs over the course of an hour. Proteins adsorbed to the HA surface included highly abundant proteins in canine saliva, antimicrobial proteins, protease inhibitors and the buffering agent carbonic anhydrase. Greater understanding of the canine AEP deepens fundamental knowledge of the early processes driving bacterial colonisation of the tooth surface and subsequent plaque accumulation.